Beyond the First Quadrant: Origin of the High Frequency Intensity‐Modulated Photocurrent/Photovoltage Spectroscopy Response of Perovskite Solar Cells. Issue 5 (9th April 2021) - Pockett, Adam; Spence, Michael; Thomas, Suzanne K.; Raptis, Dimitrios; Watson, Trystan; Carnie, Matthew J.
Abstract : The complete interpretation of small perturbation frequency‐domain measurements on perovskite solar cells has proven to be challenging. This is particularly true in the case of intensity‐modulated photocurrent/photovoltage spectroscopy (IMPS/IMVS) measurements in which the high frequency response is obscured by instrument limitations. Herein, a new experimental methodology capable of accurately resolving the high frequency response—often observable in the second and third quadrants of the complex plane—of a range of perovskite devices is demonstrated. By combining single‐frequency IMPS/IMVS measurements, it is able to construct the time dependence of the IMPS/IMVS response of these devices during their initial response to illumination. This reveals significant negative photocurrent/photovoltage signals at high frequency while devices reach steady state, which is in keeping with observations made from comparable time‐domain transient measurements. These techniques allow the underlying interfacial recombination and ion migration processes to be assessed, which are not always evident using steady‐state measurements. The ability to study and mitigate these processes is vital in optimizing the real‐world operation of devices. Abstract : The intensity‐modulated photocurrent/photovoltage spectroscopy (IMPS/IMVS) response of perovskite solar cells is accurately resolved, demonstrating that features commonly observed at high frequency in literature reports are due to artefacts caused by limitations of standard instruments. The time dependence of the IMPS/IMVS response shows clear links to effects of ion migration on the electric field and interfacial recombination rates within devices.